Pengaruh Suplementasi Besi (Fe) Dosis Tinggi Terhadap Kondisi Sel Beta Pankreas pada Tikus Putih (Rattus Norvegicus) Strain Wistar Bunting. - Aldi, Alfin Septia Putri; Kalsum, Umi; Fatmawati, Fatmawati (Journal of Issues in Midwifery, 2019)
During pregnancy, pregnant women need various nutrients. One of the nutrients need is iron. Iron functions for the formation of hemoglobin. Excess iron can increase free radicals and trigger oxidative stress. The aim of this study was to determine the effect of high doses of iron supplementation on the condition of the beta cells pancreas of the pregnant wistar white rat (Rattus novergicus). The condition of pancreatic beta cells seen is the number of beta cells calculated using a microscope with 400x magnification. Iron supplementation was given 18 days with 3 different doses (0.54mg, 1.08mg, and 2.16mg). The number of pancreatic beta cells differed significantly between the control and treatment groups (p = 0,000), the mean number of the smallest pancreatic beta cells in the group (P3) 12,17. Iron supplementation can reduce the number of pancreatic beta cells in pregnant wistar white rat (Rattus novergicus).